Behaviour, physiology and carotenoid pigmentation in Arctic charr Salvelinus alpinus - Brännäs, Eva; Nilsson, Jan; Magnhagen, Carin; Backström, Tobias (Journal of Fish Biology, 2014)
The behaviour during an exploration task and the response to a confinement stress of Arctic charr Salvelinus alpinus were evaluated. Behaviour of individuals during 90 min of exploration was classified into high and low activity. High-activity individuals had higher plasma cortisol levels following stress compared to low-activity individuals. This indicates that high- and low-activity individuals correspond to reactive and proactive stress-coping styles. Further, a pigmentation analysis showed that high-activity individuals had a higher number of carotenoid spots cm(-2) than low-activity individuals. Thus, carotenoid pigmentation, as melanin pigmentation in other salmonids, could be linked to stress-coping style in S. alpinus. (C) 2013 The Fisheries Society of the British Isles